Role of Systemic Inflammatory Response Markers in Urothelial Carcinoma - Yuk, Hyeong Dong; Ku, Ja Hyeon (Frontiers in Oncology, 2020)
Urothelial carcinoma (UC) can occur in various parts of the urinary tract and occurs in different stages and grades. The disease recurs frequently and is monitored through a series of invasive tests, such as cystoscopy or ureteroscopy, over the lifetime of an individual. Although many researchers have attempted to stratify the risks of UC, with the majority being based on cancer characteristics and host factors such as performance status, a risk classification system has yet to be fully developed. Cancer affects various parts of the body through the systemic immune response, including changes in hormones, the number and ratio of white blood cells and platelets, and C-reactive protein (CRP) or albumin levels under the influence of neuroendocrine metabolism, hematopoietic function, and protein and energy metabolism, respectively. Herein, we reviewed various systemic inflammatory response markers (SIRs) related to UC, including CRP, albumin-globulin ratio, albumin, Glasgow prognostic score (GPS), modified GPS, neutrophil-lymphocyte ratio, and platelet-lymphocyte ratio. Our aim was to summarize the role of various SIRs in the treatment of patients with UC.